Fertility in Zebu cattle (Bos indicus) after prostaglandin administration and artificial insemination - Rekwot, P.I.; Oyedipe, E.O.; Mukasa-Mugerwa, E.; Sekoni, V.O.; Akinpelumi, O.P.; Anyam, A.A. (Elsevier, 1999)
A total of 137 cycling Zebu cows, each receiving a single dose of prostaglandin PGF 2a were used in an oestrus synchronization programme on three different farms. Of the cows on the three farms, 60.6 and 90.5 percent showed over oestrus and luteolysis, respectively. Pregnancy rate to fixed time inseminations following single injection of PGF 2a was 61.4 percent for farm 1, significantly higher than the values of 45.7 and 46.9 percent for farms 2 and 3, respectively. The pregnancy rates to second service of rebred cows were 53.3, 50.0 and 50.0 percent for the three farms, respectively, with no significant differences between each. Fertility classification of the cows based on progesterone (P4) concentration showed that 6.6 percent of cows on the three farms were incorrectly diagnosed as having corpora lutea; 2.9 percent of them had incomplete luteolysis and 5.1 percent may have lost their embryos between days 21 and 45 post-insemination. The pregnancy rate was 10 percent higher in the rainy season than in the dry season. Cows with body condition scores of 3 and 4 had a higher overall pregnancy rates than those with a body condition score of 2. The findings of this study further confirm the luteolytic efficacy of prostaglandin in inducing oestrus in Zebu cattle and indicate that the nutritional status of the cows must be satisfactory before embarking on oestrus synchronization programmes.